The relationship between perfectionism, anxiety, putting performance and the yips in golf: replication of chambers & marshall (2017) - Heron, J.; Bilalic, M. (International Journal of Golf Science, 2022)
This study attempted to elucidate the effects of perfectionism and anxiety on golf putting performance and the yips by replicating a study from Chambers and Marshall (2017). Using a cross-sectional design, this study had one-hundred and seventeen participants complete an online questionnaire. This was comprised of questions relating to golfing history and included three domain-specific measures for perfectionism (Stöber, Otto, & Stoll, 2004), anxiety (Smith, Smoll, Cumming, & Grossbard, 2006) and putting performance (Chambers & Marshall, 2017). Based on mean handicap, the current sample was significantly more skilled than in the original study (20.5 in the original study versus 9.3 in the current study), yet results revealed 34.2% of participants had been affected by the yips at some point in their golfing life. Furthermore, results from the hierarchical regression analyses indicated that those who had higher levels of anxiety and higher levels of maladaptive perfectionism reported greater disruption to putting performance. Those who reported experiencing the yips did not necessarily report higher scores on the anxiety and perfectionism measures. However, anxiety did mediate the influence of perfectionism on putting performance, as in the original study from Chambers and Marshall (2017). These findings add support to the idea that anxiety and perfectionism can affect performance, however further research is needed to understand their influence on the manifestation of the yips.